Strengthening Organizational Citizenship Behavior Through Emotional Intelligence and Work Ethics - Alya Madani Sekarwangi; Yunizar; Wa Ode Zusnita Muizu (Quantitative Economics and Management Studies, 2023)
The purpose of this research is to analyze the effect of emotional intelligence and work ethics on increasing employee organizational citizenship behavior in one of the government agencies in Jakarta. The research design used in this study is a quantitative associative approach by using SPSS software, that is research that tests the causal relationship between independent variables, namely emotional intelligence (X1) and work ethics (X2) with the dependent variable, organizational citizenship behavior (Y). In conducting this research, questionnaires were distributed to 100 related samples, namely state civil servants in one of the government agencies located in Jakarta. Based on the results of the data analysis that has been carried out, there is a first hypothesis (H1), emotional intelligence has a positive and significant effect on organizational citizenship behavior and the second hypothesis (H2) is that work ethics has a positive and significant effect on organizational citizenship behavior. Hence, emotional intelligence and work ethics have positive and significant effect on organizational citizenship behavior.